A Postmodern Analysis of A3B Node: Integrating Islamic Ideology and Integral Education at SMAIT Thariq Bin Ziyad - Nayla Rahdaulia Nourabiaz; Maritza Sirin Adila; Fathia Alma Khalisa; Aliyandra Atthia Zahra; Yusril Fahmi Adam; Syafiya Mulyo Ardi (NALAR, 2026)
This study aims to provide an analysis of the A3B node, namely Akhlaq, the Qur'an, Academics, and Language, at SMAIT Thariq Bin Ziyad from a postmodern perspective. This article contributes to the effort to examine the relationship between Islamic ideology and integral education in the postmodern era as a critique of the modernist view that places Islamic ideology as something that is marginalized and considered as the cause of friction that occurs in the global landscape, and this context is then connected to the A3B node as a form of internalization of Islamic ideology and integral education. In its analysis, this study uses a qualitative method with an interdisciplinary approach, namely phenomenology and history, and is based on structural functional theory. The analysis in this study shows that the Akhlaq and the Qur'an Node are related to Islamic ideology that is internalized through school programs with contextual da'wa values, and the Academic and Language nodes are intertwined with integral education with a flexible and reflective curriculum model. In the context of postmodernism, the synthesis between Islamic ideology and integral education in the A3B node at SMAIT Thariq Bin Ziyad can be an alternative in the development of integral education by placing Islam as an active and contributing force to the complexity of thought and civilization in the contemporary era.